Constantinos Paschalidis (with contributions by Photini J. P. McGeorge and Wiesław Więckowski). The Mycenaean Cemetery at Achaia Clauss near Patras. pp. xxiii+510, 918 ills (238 photos & plans of tombs, mostly b/w; 679 col. ills, 96 accompanied by b/w dra - Dickinson, Oliver (Journal of Greek Archaeology, 2020)
This is the second publication of tombs from a large Mycenaean cemetery in Achaea to appear in two years; the other, being concerned with tombs at Ayios Vasileios, Chalandritsa (hereafter Chalandritsa) was reviewed in JGA 3 (2018), 449-451 (Aktypi 2017). The two sites both belong to a constellation of sites to the east and south-east of Patras, but there are noteworthy differences between the two. The Chalandritsa tombs were mainly excavated in rescue work carried out by members of the Ephorate of Prehistoric and Classical Antiquities of Achaea at various times between 1989 and 2001; the cemetery contained at least 45 tombs, but only about a dozen produced much useful information, and only two of these were excavated more or less intact. The volume reviewed here publishes the results of research excavations in the Clauss cemetery, carried out for the Archaeological Society between 1988 and 1992 by Prof. A. Papadopoulos of Ioannina University.